Recognition of RNA Branch Point Sequences by the KH Domain of Splicing Factor 1 (Mammalian Branch Point Binding Protein) in a Splicing Factor Complex - Peled-Zehavi, Hadas (American Society for Microbiology, 2001)
Mammalian splicing factor 1 (SF1; also mammalian branch point binding protein [mBBP]; hereafter SF1/mBBP) specifically recognizes the seven-nucleotide branch point sequence (BPS) located at 3′ splice sites and participates in the assembly of early spliceosomal complexes. SF1/mBBP utilizes a “maxi-K homology” (maxi-KH) domain for recognition of the single-stranded BPS and requires a cooperative interaction with splicing factor U2AF65 bound to an adjacent polypyrimidine tract (PPT) for high-affinity binding. To investigate how the KH domain of SF1/mBBP recognizes the BPS in conjunction with U2AF and possibly other proteins, we constructed a transcriptional reporter system utilizing human immunodeficiency virus type 1 Tat fusion proteins and examined the RNA-binding specificity of the complex using KH domain and RNA-binding site mutants. We first established that SF1/mBBP and U2AF cooperatively assemble in our reporter system at RNA sites composed of the BPS, PPT, and AG dinucleotide found at 3′ splice sites, with endogenous proteins assembled along with the Tat fusions. We next found that the activities of the Tat fusion proteins on different BPS variants correlated well with the known splicing efficiencies of the variants, supporting a model in which the SF1/mBBP-BPS interaction helps determine splicing efficiency prior to the U2 snRNP-BPS interaction. Finally, the likely RNA-binding surface of the maxi-KH domain was identified by mutagenesis and appears similar to that used by “simple” KH domains, involving residues from two putative α helices, a highly conserved loop, and parts of a β sheet. Using a homology model constructed from the cocrystal structure of a Nova KH domain-RNA complex (Lewis et al., Cell 100:323–332, 2000), we propose a plausible arrangement for SF1/mBBP-U2AF complexes assembled at 3′ splice sites.